Association of Fish Consumption with Prevalence of Depression among Men and Women - A Literature Review - Manzur Kader (International Journal of Medical Research, 2013)
Background: Depression is a frequent mental disorder characterized by a high level of morbidity in both men and women and has become a leading cause of disability as measured by Years Lived with Disability (YLDs). Fish is major source of long-chain omega-3 polyunsaturated fatty acids (ω-3 PUFAs) that are important in the development of the central nervous system. Lower ω-3 PUFA levels have been found in red blood cell membranes among depressed people in some studies, but trial evidence that has examined the effect of ω-3 PUFAs on depression is very limited. Objectives: This review aims to find out if there is any association of fish consumption or dietary intake of omega-3 PUFAs with prevalence of depression among adult men and women. Methods: Research articles were searched through database PubMed by using search string “fish consumption AND depression”. The inclusion criteria were being the articles based on studies dealing with omega-3 PUFAs in fish in relation to depression or mood disorders among men and women. Results: Fish consumptions or intake of ω-3 PUFAs were inversely associated with the prevalence of depressive symptoms among men and women. There were gender differences in the results where one study demonstrated the association in men; two studies demonstrated the association in women and one study found association in both men and women. Conclusion: High dietary intakes of fish and omega-3 fatty acids appear to be related to a lower risk of depression in all the studies included in this review, although there is inconsistency with gender.